O DOCUMENTO ORIENTADOR ATPC SEDUC-SP COMO INSTRUMENTO DE FORMAÇÃO CONTINUADA: UMA ANÁLISE A PARTIR DA TEORIA DA ATIVIDADE DE LEONTIEV - IARA APARECIDA GOMES SILVA (2023)
This dissertation is linked to the Graduate Program in Education at the Federal University of Mato Grosso do Sul, at the master's level, and is part of the line of research Teacher Training and Educational Policies. The general objective of this research was to understand the conceptual unity between the need and objective of continuing teacher training, based on Leontiev's Activity Theory (AT), based on the ATPC Guiding Document of the state education network of São Paulo. It originated from the objective of carrying out a critical analysis of the guiding document of the ATPC (Collective Pedagogical Work Class) of the State of São Paulo. It originated from the objective of carrying out a critical analysis of the guiding document of the ATPC (Collective Pedagogical Work Class) of the State of São Paulo in the light of the Activity Theory of Aleksei Nikolaievitch Leontiev. The research uses an ontological approach and is developed in three stages: bibliographical, documental, and systematization and analysis of results. A literature review was carried out from theorists who discuss Teacher Training and the Historical-Cultural Theory, as well as Documentary Research, using as data sources the ATPC regulatory documents produced by the teaching network of the State Department of Education of the State of São Paulo (SEDUC), which is the locus of the investigation. In the documentary research, it was possible to retrieve the regulatory framework and identify the most important concepts about ATPC defined by SEDUC-SP for the state education network in the state of São Paulo. The method for document analysis is Leontiev's Theory of Activity, as one of the developments of the Historical-Cultural Theory, associated with an education that starts from historical-cultural psychology to defend a teaching-learning process that is meaningful, diversified and stimulating, aiming at understanding the relationships between culture, learning and human development. In relation to the guiding problem of the research “How does the conceptual unity between the need and the objective of the continuous formation of teachers, from Leontiev's theory of activity, for teachers in the State of São Paulo occur?”. It was observed that the Document follows the foundations of Leontiev's Theory and promotes the guarantee of the activity of continued formation of teachers in the school scope, with organized space for the discussion in relation to the teaching, anchored in the pedagogical proposal motivated by the need and objective of the local historical and social contexts. However, it is suggested that other studies will promote the relationship between the Guiding Document and its effectiveness in the practical field.